2021
DOI: 10.1111/ijag.15894
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the replacement of silica by boron trioxide on the properties of bioactive glass scaffolds

Abstract: The dissolution properties and bioactivity of bioactive glasses (BGs) are mainly determined by their glass network structure. Silicate BGs are the most famous representatives of BGs. However, borate BGs have gained increasing interest due to their faster degradation rate. By adding boron trioxide in the silicate network, borosilicate BGs can be fabricated with controlled degradation rates. Since the kind and amount of network former determines the resulting BG properties, the aim of this study was to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…al. also show that this type of result in paper title of paper is influence of the replacement of silica by boron trioxide on the in paper properties of bioactive glass scaffolds 13 .…”
Section: Bioactive Glasses Analysis By X-raymentioning
confidence: 62%
“…al. also show that this type of result in paper title of paper is influence of the replacement of silica by boron trioxide on the in paper properties of bioactive glass scaffolds 13 .…”
Section: Bioactive Glasses Analysis By X-raymentioning
confidence: 62%
“…In general, the presence of hBN nanoparticles appeared to enhance the HA-forming ability of bioactive glass starting from certain concentrations, presumably due to their high surface area. Similarly, in a different study, hydroxyapatite precipitation was reported on the surface of boron nitride nanoparticles in 5 days when immersed in simulated body fluid [ 43 ]. This result supports the increase in bioactivity seen in bioactive glass scaffolds containing hBN nanoparticles.…”
Section: Resultsmentioning
confidence: 95%
“…This behavior may be correlated with the loose network of the borate glasses. Unlike silica, the coordination number of boron prevents the full formation of the 3D network structure, causing the boron-based glass to have lower chemical stability [ 43 ]. It is also known that ions such as Na + , K + , Mg 2+ , and (BO 3 ) −3 dissolve in solution and all CaO in the glass reacts with phosphate ions in SBF to form HA and the theoretical weight loss of fully transformed 13-93B3 bioactive glass scaffolds is 67% [ 3 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…2) and cellular reactions concerning silica-based BG. 61 The phenomenon of BO 3 triangles and BO 4 tetrahedra coordination that constitutes a continuous system of vitreous boric oxide is an exciting feature of the borate glass structure; besides, as more and more of these units assemble, they constitute well-defined and stable borate groups, such as diborate, triborate, and tetraborate, that also form the glass networks. 63,64 In contrast to silicate or phosphate glass, adding a certain molar percentage of alkali ions R 2 O (where R can be Li, Na, or K) to B 2 O 3 -based glasses alters the network model by decreasing the boroxol rings.…”
Section: Borate Bioactive Glass (Bbgs)mentioning
confidence: 99%